1984
DOI: 10.1017/s1014233900000109
|View full text |Cite
|
Sign up to set email alerts
|

The Indigenous Goats of Nigeria

Abstract: The three breeds of goat in Nigeria -Sahel (Sh), Red Sokoto (RS) and West African Dwarf (WAD) -are described. The performance of the latter two is illustrated in the tables. RESUMELes trois races caprines du Nigéria -Sahélienne (Sh) , Sokoto rouge (RS) et naine d'Afrique orientate (WAD) -sont décrites; des tableaux illustrent les performances des deux dernières races. RESUMENSe describen las tres razas de ganado caprino de Nigeria: Sahel (Sh), Red Sokoto (RS) y West kfrican Dwarf (WAD). En los cuadros se expon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 2 publications
2
24
0
Order By: Relevance
“…According to [23], majority (75%) of female WAD goats had their first kids at ages ranging between 14 and 20 months, which agreed with an earlier report [10] that the overall mean of age at first kidding was 18.5 ± 1.2 months. Doe prolificacy was 1.70 ± 0.04 [20] and was markedly affected by year of birth and parity [20] [25].…”
Section: Reproductive Traitssupporting
confidence: 82%
See 3 more Smart Citations
“…According to [23], majority (75%) of female WAD goats had their first kids at ages ranging between 14 and 20 months, which agreed with an earlier report [10] that the overall mean of age at first kidding was 18.5 ± 1.2 months. Doe prolificacy was 1.70 ± 0.04 [20] and was markedly affected by year of birth and parity [20] [25].…”
Section: Reproductive Traitssupporting
confidence: 82%
“…These include fertility, prolificacy, annual doe productivity and kid survival rate of WAD goats are shown in Table 1. Key literature sources for these information include the detailed review of goat breeds of Nigeria by [10] and scientific papers by [19]- [24], as well as the classical treatise "Goat Breeds of the World" [1].…”
Section: Reproductive Traitsmentioning
confidence: 99%
See 2 more Smart Citations
“…The genetic distance calculated according to Nei (1972) showed that the smallest genetic distance was between the Maradi and Sahel goats with a genetic distance of 0.025. Ngere et al (1984) reported that population of the Maradi spread South and East from Sokoto through the savannah belts giving rise to the Kano Brown and, further east, to the Sahel types of Borno State, meaning that Sahel goat could be a strain of Maradi. Hence, a reason for the least genetic distance observed.…”
Section: Discussionmentioning
confidence: 99%